Water Quality Assessment, and Suitability for Irrigation Purposes of Lesser Zab River, Northern Iraq. - A. Alsanjari, Abd alsattar; S. Alqattan, Aassal (Iraqi Journal of Science, 2023)
This research was conducted to investigate the water quality of the lesser Zabriver, to evaluate the water suitability for agricultural usings and report the effect ofhuman activities on this water. Samples were collected along the river streamstarting from Dukan area till the convergence with Tigris River. All the tests wereconducted at the labs of Environmental sciences and Technology College /University of Mosul and Erbil water project/Erbil city.The results of using Piper diagram showed that the water is alkine, due to the effect of the origional rock's components of that area on the water quality. While the using of Stiff diagram elucidate that the water samples contain ions belong to the area of the lesser Zab crossing which have carbonic formation. The using of Richard diagram showed that the quality of the water in all the samples tested, is good and suitable for irrigation. Also the water of the lesser Zab showed no signs ofpolluted effects on the Tigris river after converging due to the length of the lesserZab and the dilution happening to its polluters along its path